Human trafficking: a South African perspective - Yesufu, Shaka (Penerbit Universiti Kebangsaan Malaysia, 2020)
Human trafficking is a lucrative global crime. Organised criminals continue to ply their trade with impunity. They profit from this illicit trade. Victims of trafficking are transported from their places of origin to destinations both within and outside their countries. They are promised better life by the traffickers, who sometimes coerce victims to work against their will upon arrival in their destination countries. In some instances, the victim’s travel documents are seized by the traffickers. The purpose of this article is to highlight the impact of human trafficking internationally and in South Africa. The researcher relies on an extensive literature review and the collection of secondary data. Secondary data in the context of this research is the process of reviewing several data already collected from previous studies relating to the research topic ‘human trafficking’. The research is informed by the labeling theory. The researcher highlights some of the challenges faced by policing human trafficking both as organised and borderless crime. The researcher recommends both the use of information technology and intelligence-led policing for combating the growing trend of human trafficking. It is also recommended that both national and regional co-operation needs to be strengthened globally to combat human trafficking.